A ROLE OF ARGININE DEIMINASE FROM STREPTOCOCCUS PYOGENES M49-16 IN PROMOTING INFECTION AND INHIBITION OF ENDOTHELIAL CELL PROLIFERATION - E. A. Starikova; A. B. Karaseva; L. A. Burova; A. N. Suvorov; A. V. Sokolov; V. B. Vasilyev; I. S. Freidlin (Медицинская иммунология)
Arginine deiminase is a bacterial enzyme that hydrolyses arginine with citrulline and ammonia formation. In recent years, increasing evidence is reported about in vitro and in vivo anti-angiogenic action of arginine deiminase from Mycoplasma spp. Our studies have shown that arginine deiminase from Streptococcus pyogenes M22 exerts similar effects, i.e., inhibits proliferation and other endothelial cell functions related to angiogenesis. To confirm a leading role of arginine deiminase, as a factor responsible for the anti-proliferative effect, we have constructed an isogenic S. pyogenes M49-16 mutant unable to express arginine deiminase. A comparative analysis of anti-proliferative activity of original S. pyogenes M49-16 strain and its isogenic mutant with arginine deiminase gene deletion (M49-16delAD) was performed, using an endothelial EA.hy926 cell line. The bacterial supernatantes obtained by sonication of S. pyogenes M49-16 and M49-16delAD were tested. The ability of S. pyogenes M49-16 and M49-16delAD supernatantes to hydrolyze arginine was assessed. Moreover, we compared effects of the Streptococcus supernatantes upon proliferative activity of endothelial cells and their distribution through the cell cycle phases.Supernatantes from original S. pyogenes 49-16 strain were shown to inhibit endothelial cell proliferation to a significant degree (down to 50% of controls). This effect was due to its arginine hydrolyzing activity, i. e. addition of exogenous arginine to the medium resulted into recovery of the cell proliferation levels. The supernatante from S. pyogenes M49-16delAD showed a lower ability to hydrolyze arginine as compared to the supernatante of original strain. Culturing of endothelial cells supplied with S. pyogenes M49-16delAD supernatantes resulted into reduction of their proliferative activity by 10% of control values. Analysis of the cell cycle distribution was concordant with these results. S. pyogenes M49-16 supernatante caused a decrease in S-phase cell fraction by 20% against controls. With a supernatants from S. pyogenes M49-16delAD, such drop in DNA-synthesizing cell ratio was significantly weaker (by only 5% of the control). These results reveal new pathogenetic mechanisms of endothelial dysfunction during streptococcal infection and suggest anti-angiogenic potential of streptococcal arginine deiminase.